Millions of user credentials for popular sites sold on dark markets. Issue 6 (June 2016) - Unknown
Abstract : Databases containing user credentials for a number of major sites have suddenly become available on underground cybercrime forums and dark markets, even though the breaches that led to the data leaks are years old in many cases.